Investigations on Alkanediols as Alternative Preservatives in a Nonionic Hydrophilic Cream - Melanie Sigg; Rolf Daniels (MDPI AG, 2020)
Alkanediols are often used as alternative antimicrobial preservatives for dermal formulations, e.g., hydrophilic creams. These substances show an antimicrobial effect due to their amphiphilic structure. At the same time, their amphiphilic behavior enables various interactions with the cream base itself. Therefore, the effect of four different alkanediols, namely 1,2-pentanediol, 2-methyl-2,4-pentanediol (hexylene glycol), 1,2-hexanediol, and 1,2-octanediol on the physical stability of a nonionic hydrophilic cream was investigated. Further, the incorporation of the alkanediols into lamellar structures of the cream was evaluated using differential scanning calorimetry (DSC) and small-angle X-ray scattering (SAXS) measurements. The interaction with the mixed crystals of the cream was found to increase with raising alkyl chain length of the added alkanediol. As a result, consistency and stability of the cream are slightly impaired. A test for efficacy of antimicrobial preservation according to the European Pharmacopoeia (Ph.Eur.) revealed that the antimicrobial activity is directly linked to the length of the alkyl chain of the alkanediols. 2-Methyl-2,4-pentanediol differs from both findings. This compound has non-vicinal hydroxy groups which result in a reduced amphiphilicity compared to the others. Consequently, it has a smaller impact on the colloidal structure of the cream and shows a comparatively low antimicrobial activity.